Effectiveness of Cashew Product Marketing Strategy at UD Cashew Mubaraq Lombe, Lahundape Village, West Kendari District, Kendari City - Desty Rismayanti; Sukmawati Abdullah; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
UD Cashew Mubaraq Lombe is a trading business that provides a variety of snacks typical of the Southeast Sulawesi region made from cashew nuts. A good marketing strategy is needed to introduce the products at UD Mete Mubaraq Lombe to the public. Marketing strategy is also one of the factors that can direct the level of marketing effectiveness that can be achieved. The effectiveness of the marketing strategy is the extent to which the company achieves the goals that have been agreed upon or previously set. Thus it can be interpreted that if marketing can be carried out correctly as planned or targeted according to the company's goals that have been set, it can be said that the marketing is effective. This study aims to describe the marketing strategy applied by UD Cashew Mubaraq Lombe in increasing the competitive advantage of the products being marketed and to determine the marketing strategy of UD Cashew Mubaraq Lombe's products. The research was carried out in the Lahundape Village, West Kendari District, Kendari City. The study is conducted using qualitative descriptive analysis. The dependent variables are product (X1), price (X2), promotion (X3), place (X4), service (X5), process (X6), people (X7), and physical evidence (X8). The independent variable (Y) is the marketing strategy applied by UD Mete Mubaraq Lombe. The results showed that all the methods used by UD Cashew Mubaraq effectively increased sales volume.